2017
DOI: 10.1093/her/cyx053
|View full text |Cite
|
Sign up to set email alerts
|

Impact of patient education on influenza vaccine uptake among community-dwelling elderly: a randomized controlled trial

Abstract: This randomized controlled trial aimed to test the effectiveness of brief face-to-face patient education in increasing influenza vaccination rate among elderly in the community. Recruitment and intervention were conducted at two general outpatient clinics in Hong Kong. 529 eligible patients were randomly assigned to intervention or control group with 1:1 allocation ratio. Patients in the intervention group received 3-min one-on-one verbal education by medical students and a pamphlet regarding influenza vaccina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 18 publications
1
28
0
Order By: Relevance
“…15 Study done in Hong Kong by Ka Chun Leung et al demonstrated an increase of 8.6% in uptake of vaccination following a 3 minutes one-on-one verbal health education. 16 One of the limitations of institution-based study such as ours is lack of generalizability to other institutions and areas of the country. The sample size was also small which may yield skewed results.…”
Section: Discussionmentioning
confidence: 86%
“…15 Study done in Hong Kong by Ka Chun Leung et al demonstrated an increase of 8.6% in uptake of vaccination following a 3 minutes one-on-one verbal health education. 16 One of the limitations of institution-based study such as ours is lack of generalizability to other institutions and areas of the country. The sample size was also small which may yield skewed results.…”
Section: Discussionmentioning
confidence: 86%
“…Although provaccine educational materials have been previously studied, researchers have primarily assessed parental vaccine hesitancy and intent to vaccinate, 18,19,28,29 have used a different time line or mode of delivery (eg, text-message reminder), 29 or have focused on adolescent-only, adult, or pregnant women populations. [30][31][32][33][34] This study is 1 of the first studies in which an experimental design is used to evaluate the effect of an intervention with educational handouts in the clinic setting on child influenza vaccine receipt. We found that a brief educational intervention for caregivers before seeing a health care provider may have lasting effects by helping to increase pediatric vaccine uptake by the end of the season, and we found that an educational handout that is based on national data may improve influenza vaccination rates on the clinic visit day.…”
Section: Discussionmentioning
confidence: 99%
“…The study designs are divided into 34 cross-sectional studies of which 13 studies were developed by means of a secondary analysis of already existing data [11, 12, 14, 15, 19-21, 28-30, 38, 39, 41] and two cross-sectional studies following a qualitative study design [26,32], four randomized controlled trials [43][44][45][46], two systematic reviews [47,48], two cohort studies [49,50] and two theoretical reviews [51,52].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…The number of participants older than 65 years of study samples ranges from 11% to 100% of all initially included study participants (n= 19.604.711) from across the globe in countries from four continents and in following care settings: Community-dwelling or non-institutionalized citizens [9, 15, 21, 23, 27-31, 33, 36, 39, 42, 48, 50], nursing homes [12,38], combined settings [32,37], outpatient clinics [44], hospitals [18,22], primary care centres/clinics or practices [24,26,43,45], home-based primary care settings [10] and data bases such as the Medicare registry, national vaccine industry or settings of health services/insurance authorities [13,40,46]. In 12 studies, details about the care setting of the participants were not indicated [11,14,16,17,19,20,25,34,35,41,47,49].…”
Section: Study Characteristicsmentioning
confidence: 99%